construction of Criterion - Referenced test in mathematics for the seventh grad (Damascus University Journal of educational and Psychologyical sciences, 2022)
The current research examines the use of classical theory in the construction of the test of reference in the mathematics of the seventh grade, where the Criterion – Referenced test was constructed of (50) single choice of multiple under four alternatives, one of which represents the correct answer.The test was carried out on a sample of 580 students from the seventh grade. The test included the entire curriculum and the analytical descriptive method was applied at the end of the academic year.The accuracy of the correlation coefficients was statistically significant,with the highest value of 0.96.The validity of the test was also verified. Stability was also studied using the Cord-Sung-21 coefficient, as well as semi-retail stability and repeatability ( high ). As for the ease of vocabulary, it was calculated for the test items, and they were all within the normal limits except items (1-22-29) and therefore excluded. Also, for the ability indicators, the distinguishing characteristics of the test were within the natural limits except for (18)Test items (59) items.The Wright-Smith map shows that individuals tend to be centered around their average power value within two standard deviations except for a small number Of the individuals did not exceed (12) individuals, and the stability factor was studied as well .Thus, the study achieved its objectives, the most important of which is to obtain a test included in mathematics for the seventh grade. As for the ability of discrimination, the values of the coefficients of discrimination of items were consistent between them and restricted between (1.32 - 0.79) Exceed (0.10) and the largest (0.06).
Keywords: classical theory، criterion referenced test